PENGARUH IMBANGAN TAPE KETAN HITAM DAN BUAH NAGA MERAH TERHADAP MUTU ORGANOLEPTIK PADA SNACK BAR DIABETES MELITUS - Hapsari, Agustina Indri; Widartika, Widartika (Poltekkes Kemenkes Bandung, 2025)
Oxidative stress in DM patients can be inhibited by consuming foods that are high in antioxidants. Black glutinous tape and red dragon fruit were chosen as snack bar ingredients because they contain high fiber, low Glycemic Index (IG), and high antioxidants. The study aimed to analyze the organoleptic quality of the formulation of black glutinous rice tape snack bars and red dragon fruit. The design of this study was experimental with a Complete Random Design (RAL) consisting of independent variables and dependent variables. The independent variable was the balance of black sticky rice tape: red dragon fruit F1=75:25, F2=60:40, and F3=50:50. The dependent variable is the organoleptic quality of the Snack Bar DM product. The hedonic test involved 30 moderately trained panelistsThe analysis used was the One-Way Anova test and the Duncan follow-up test. The results showed that there was no difference in terms of color, aroma and texture in the three black glutinous rice snack bar and red dragon fruit snack bar formulas. However, there were organoleptic differences in taste in various balances of black glutinous rice tape snack bars and red dragon fruit p=0.032. Duncan's test results show that the best snack bar flavor is a snack bar with formula 3 with a balance of 50% black glutinous tape: 50% red dragon fruit.